Faces e interfaces do cinema de poesia – A insustentável leveza do ser e a forma lírica de narrar a liberdade - Pedrolo, Fabiana Maceno Domingos (2018)
This research presents an analysis of the cinematographic work The Unbearable Lightness of Being (1987) directed by Philip Kaufman, a movie based on the homonymous literary work of the Czech writer Milan Kundera. Based on their main characters – Tereza, Tomaz, Sabina and Franz –, the preponderant characteristics of these characters were pointed out, aiming at comparing them in terms of the perception of freedom that each presents, as well as the inherent aspects of the poetry cinema present in this production which help in the construction of the imaginary and literary senses. For such an approach, it was necessary as theoretical reference, the authors found in the philosophy that conceptualize and treat the theme of freedom as Jean-Paul Sartre and Simone de Beauvoir, philosophers considered referential about the main existentialist current guiding the term concept. Aiming at the confluence between literature, cinema and philosophy, this study proposes, above all, the poetic interpretation of a cinematographic work, the amplification of meanings through the lyrical elements and also, corroborate so that the characteristic aspects to the cinema of poetry, proposed by Pier Paolo Pasolini, are identified and recognized even in postmodern works, produced long after the filmmaker, such as Lavoura Arcaica (2001) by Luiz Fernando Carvalho or the films of Peter Greenway, whose ideas depart from the images to the text and not the other way around. In addition to Pasolini (1981), Carlos Melo Ferreira (2004) and Andrei Tarkovski (1998) were consulted to give subsidies in order to understand how the field of poetry is constructed within cinematographic works.